LITERASI DIGITAL SEBAGAI UPAYA MENINGKATKAN KUALITAS TENAGA DIDIK DAN PESERTA DIDIK - Endang Rukmiati (An Nuur, 2022)
Information technology is an important part of education, especially educators and students. Students in today's digital era are required to learn technology so that information is not left behind and can be proactive in using media. One of the impacts of technology in the field of education is the emergence of teacher innovations in learning which is also known as e-learning. E-learning is learning carried out by electronic means in video, computer, and audio formats.The students in this case are the teachers. The teacher is a very important faktor in improving the quality of learning. However, there are still educators who lack adequate digital literacy skills. Currently teaching literacy is a skill that must be possessed by teachers. There is a positive side with the pandemic in Indonesia, learning is done online (distance learning), with technology that supports all needs in the teaching and learning process. Advances in information technology in the field of education can bring convenience to teachers or students and students in the learning process.The benefits of learning digital skills are the ability to access information quickly, saving time and money, making learning easier because it is not limited by time. In an effort to improve the quality of teachers in teaching in today's digital era, namely by providing lessons to teachers regarding the use of technology for learning, understanding conditions during learning, providing linkages between students when learning. As educators, they must provide education on how to use technology properly and correctly, conditioning when learning so that students do not feel bored and bored. Keyword : digital literacy, quality of students, students